Development of origin-destination table covering EDSA bus routes covering routes with turnaround points from South to Northwest Metro Manila - Chua Yap, Jake Aaron T.
Epifanio De Los Santos Avenue (EDSA) is the main arterial road most motorists use everyday. Motorist often blame buses as the primary source of congestion experienced along this arterial road. To validate this information, this research focused on identifying the terminals with the most demand by studying the trip pattern of bus passengers with the help of developing the passenger Origin-Destination (OD) table per bus routes along EDSA road. Boarding-Alighting Survey data of Mega Manila Public Transportation Planning Support System is used to develop the OD table for EDSA bus routes. The development of OD table per route is modified to derive the bus occupancy and trip distribution of passenger per route. Based on the findings passenger occupancy per bus significantly drops once bus reached terminals where other modes of public transit are available. It was also observed that once bus reached the central business district terminals namely; Ortigas Station and Ayala Station, these stops have high demand count for boarding and alighting passengers.